2016
DOI: 10.1109/tmm.2016.2531978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Sonification Strategies for Guidance Tasks

Abstract: International audienceThis article aims to reveal the efficiency of sonification strategies in terms of rapidity, precision and overshooting in the case of a one-dimensional guidance task. The sonification strategies are based on the four main perceptual attributes of a sound (i.e. pitch, loudness, duration/tempo and timbre) and classified with respect to the presence or not of one or several auditory references. Perceptual evaluations are used to display the strategies in a precision/rapidity space and enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…In conclusion, our findings revealing that on-line evaluation of perceptual inundation in schizophrenia is related to off-line evaluation supports the relevance of identifying acoustic triggers related to sensory gating and inundation. This should enable the development of future perceptual remediations in schizophrenia [1,18] using synthetic sounds that can be precisely controlled [5,6,15,38,44] such as environmental and immersive sounds in order to treat sensory gating deficit by teaching the patients, with an attentional procedure that focuses on the auditory processing of specific acoustic features [8]. The present study may enable us to propose an attentional control on acoustic features reflecting non-stationarities in the signal, in order to reduce inundation, overwhelming and distraction by external sensory stimuli in patients’ real sonic world.…”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, our findings revealing that on-line evaluation of perceptual inundation in schizophrenia is related to off-line evaluation supports the relevance of identifying acoustic triggers related to sensory gating and inundation. This should enable the development of future perceptual remediations in schizophrenia [1,18] using synthetic sounds that can be precisely controlled [5,6,15,38,44] such as environmental and immersive sounds in order to treat sensory gating deficit by teaching the patients, with an attentional procedure that focuses on the auditory processing of specific acoustic features [8]. The present study may enable us to propose an attentional control on acoustic features reflecting non-stationarities in the signal, in order to reduce inundation, overwhelming and distraction by external sensory stimuli in patients’ real sonic world.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to comparing the effects of auditory display to other intraoperative modalities such as augmented reality [16], virtual reality, and conventional navigation, evaluations should include comparisons of multiple auditory display methods, which none of the reviewed literature provided. Investigations into comparing multiple methods for auditory display for 1-dimensional guidance tasks suggest expanding such evaluations to 2-D and 3-D tasks [30]. Such an approach could be taken within the context of multidimensional tracked instrument placement, for instance, for needles [2, 3], aspirators, or continuum robots [7].…”
Section: Discussionmentioning
confidence: 99%
“…When the specific task allows to concentrate on one stream at a time and switch attention if needed, two streams can be leveraged as well. Many researchers already highlighted the importance of auditory scene analysis principles and psychoacoustics in auditory display design [1,5,31,8,32]. Pitch: Perceived pitch is a multi-dimensional quality that consists of rectilinear height and circular chroma, which repeats every octave [33].…”
Section: Psychoacousticsmentioning
confidence: 99%
“…Many authors like [6,32,8] already identified pitch, loudness, sharpness, roughness and beating as potential parameters for psychoacoustic sonification.…”
Section: Psychoacousticsmentioning
confidence: 99%